KAITAN PEMBELAJARAN BERBASIS MASALAH DENGAN KEMAMPUAN SELF-EFFICACY SISWA - Reflina Reflina (State Islamic University of North Sumatra, 2018)
Self-Efficacy is a positive attitude that an individual can make himself able to develop a positive assessment both to themselves and to the environment / situation. According to Bandura's social cognitive theory, self-efficacy beliefs influence people's choices in making and carrying out the actions they are pursuing. Self-efficacy measurement of a person based on three dimensions, namely: magnitute, Strength, Generality. Problem-based learning is a learning that demands students' mental activity optimally in learning critical thinking, problem-solving skills, and gaining knowledge about the essence of the subject matter in understanding a student's concept or concept, principles and mathematical skills in the form of ill-stucture or open-ended through stimulus